Expression of the p53 oncogene in acute myeloblastic leukemia (The Rockefeller University Press, 1986)
We have investigated whether the p53 oncogene is expressed in the blast cells of patients with acute myeloblastic leukemia. p53 protein was detected in the blast cells of 19 out of 34 patients, but not in normal myelopoietic cells. We find a highly significant correlation between p53 protein synthesis in leukemic blast cells and the secondary plating efficiency of these cells (p = 0.0001). The latter provides an estimate for the self renewal capacity of progenitor cells in the blast population. These data indicate that p53 may be involved in leukemic stem cell renewal.